Correction to: Phenotypic characterization of X-linked hypophosphatemia in pediatric Spanish population - Enrique Rodríguez-Rubio; Helena Gil-Peña; Sara Chocron; Leire Madariaga; Francisco de la Cerda-Ojeda; Marta Fernández-Fernández; Carmen de Lucas-Collantes; Marta Gil; María Isabel Luis-Yanes; Inés Vergara; Juan David González-Rodríguez; Susana Ferrando; et al. (Orphanet Journal of Rare Diseases, 2021)
An amendment to this paper has been published and can be accessed via the original article.